2019
DOI: 10.3390/microorganisms7110558
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Colistin-Resistant Escherichia coli ST695 Harboring the Chromosomally-Encoded mcr-1 Gene

Abstract: Enterobacteriaceae having chromosomally-encoded mcr-1 is rarely reported. In this study, we recovered a chromosomal mcr-1 carrying Escherichia coli, designated HeN100, from the feces of a diarrheal pig in China. Antimicrobial susceptibility testing showed that HeN100 was resistant to three aminoglycosides, twelve β-lactams including three carbapenems, one phenicol, two tetracyclines, two fluoroquinolones, nitrofurantoin, and colistin tested. Oxford Nanopore MinION sequencing revealed that the complete genomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Our bioinformatic analysis showed that the mcr-1 gene on the chromosome in strain S530 was flanked by IS Apl1 . Our finding corroborates the hypothesis that the insertion of the mcr-1 gene into the bacterial chromosome is mediated by IS Apl1 ( Peng et al, 2019 ). However, in our case, the chromosomal mcr-1 gene was found to be of plasmid origin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our bioinformatic analysis showed that the mcr-1 gene on the chromosome in strain S530 was flanked by IS Apl1 . Our finding corroborates the hypothesis that the insertion of the mcr-1 gene into the bacterial chromosome is mediated by IS Apl1 ( Peng et al, 2019 ). However, in our case, the chromosomal mcr-1 gene was found to be of plasmid origin.…”
Section: Discussionsupporting
confidence: 90%
“…The genetic arrangement of chromosome-borne mcr-1 in S530 was investigated. The chromosomal mcr-1 was adjacent to IS Apl1 and the pap2 gene, and they consisted of a “IS Apl1 - mcr-1 - pap2 ” structure, which is commonly presented in chromosome-borne mcr-1 harbored strains ( Peng et al, 2019 ). However, to our surprise, the IncN/IncQ1 replicon and repA gene were identified as a sequence surrounding the mcr-1 gene, indicating a plasmid origin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our bioinformatic analysis showed that the mcr-1 gene on the chromosome in strain S530 was flanked by ISApl1. Our finding corroborates the hypothesis that the insertion of the mcr-1 gene into the bacterial chromosome is mediated by ISApl1 (Peng et al, 2019). However, in our case, the chromosomal mcr-1 gene was found to be of plasmid origin.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, we found one chromosome-encoded mcr-1 in strain S530, which was, however, disrupted by ISVsa5. So far, a chromosome-embedded mcr-1 in Enterobacteriaceae has been rarely reported (Falgenhauer et al, 2016;Peng et al, 2019). Our bioinformatic analysis showed that the mcr-1 gene on the chromosome in strain S530 was flanked by ISApl1.…”
Section: Discussionmentioning
confidence: 74%